Immunogenic particles with a broad antigenic spectrum stimulate cytolytic T cells and offer increased protection against EBV infection ex vivo and in mice - Zyl, Dwain George van; Tsai, Ming-Han; Shumilov, Anatoliy; Schlehe, Bettina; Fluhr, Herbert; Delecluse, Henri-Jacques (PLoS pathogens, 2018)
The ubiquitous Epstein-Barr virus (EBV) is the primary cause of infectious mononucleosis and is etiologically linked to the development of several malignancies and autoimmune diseases. EBV has a multifaceted life cycle that comprises virus lytic replication and latency programs. Considering EBV infection holistically, we rationalized that prophylactic EBV vaccines should ideally prime the immune system against lytic and latent proteins. To this end, we generated highly immunogenic particles that contain antigens from both these cycles. In addition to stimulating EBV-specific T cells that recognize lytic or latent proteins, we show that the immunogenic particles enable the ex vivo expansion of cytolytic EBV-specific T cells that efficiently control EBV-infected B cells, preventing their outgrowth. Lastly, we show that immunogenic particles containing the latent protein EBNA1 afford significant protection against wild-type EBV in a humanized mouse model. Vaccines that include antigens which predominate throughout the EBV life cycle are likely to enhance their ability to protect against EBV infection.
Gesehen am 23.01.2019